Seismic damage assessment of RC structures under shaking table tests using the modified direct stiffness calculation method. (15th January 2017) - Yang, Y.; Yang, Y.B.; Chen, Z.X.
Highlights: This is the first time to solve the 3D frame structure with limited sensors by using the improved DSC method. The stiffness variation index (SVI) adopted is better than most others. The present results were compared against with the vibration data and damage history observed of a 12-story RC frame model under shaking table test of 62 scenarios, and was shown to be consistent. Both the full 3D finite element model and simplified cantilever model were used in the simulation. Abstract: The modified direct stiffness calculation (DSC) method for application to damage detection of RC frames based on the stiffness variation index (SVI) is comprehensively studied. Judging from the fact that few techniques were successfully applied to field problems, the objective herein is to apply the modified DSC method to RC frames, and to ensure that it really works. The vibration data recorded of a 12-story RC model frame under a series of shaking table tests (62 scenarios under four earthquakes of various levels) were adopted. The SVI adopted is based on two key parameters: (1) the modal curvature, which is more sensitive to structural damage than the mode shape frequently used, and (2) the modal moment, which is rather insensitive to ambient noises, as it is calculated from the force equilibrium condition . By comparing the present results with those based on a typical index (MDLAC) and the damage status of the frame in the tests, it is concluded that the modified DSC method, along with the SVI, can be reliably applied to the damage detection of RC frames in practice.